2019
DOI: 10.1002/wer.1202
|View full text |Cite
|
Sign up to set email alerts
|

Trace and bulk organics removal during ozone–biofiltration treatment for potable reuse applications

Abstract: This study investigated impact of ozone/biological activated carbon (BAC) filtration design and operational parameters on contaminants of emerging concern (CEC) and bulk organics removal over 450 days of operation. Two parallel BAC filters with identical media and influent were maintained, each at a different empty bed contact time of 10 and 20 min. This study captured the CEC removal performance of a BAC filter over an extended operational period after treating 65,000 bed volumes. Ozone system was operated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…The removal of iohexol decreased from 100% to 60% in GAC15A after 21,000 BV ( Figure 6). Meprobamate is weakly reactive with ozone and has been shown to be removed by adsorption on GAC (Gerrity et al, 2012;Sundaram et al, 2019). Meprobamate was detected in the last two sampling events, showing that the removal decreases with increasing BV, again consistent with a low log K ow 0.7.…”
Section: Cec Removal In New Gac Mediamentioning
confidence: 60%
See 2 more Smart Citations
“…The removal of iohexol decreased from 100% to 60% in GAC15A after 21,000 BV ( Figure 6). Meprobamate is weakly reactive with ozone and has been shown to be removed by adsorption on GAC (Gerrity et al, 2012;Sundaram et al, 2019). Meprobamate was detected in the last two sampling events, showing that the removal decreases with increasing BV, again consistent with a low log K ow 0.7.…”
Section: Cec Removal In New Gac Mediamentioning
confidence: 60%
“…Desorption of a compound indicates that it was previously removed by adsorption and not biodegradation. Sundaram and Pagilla (2019) showed that more than 90% of sucralose was removed by adsorption onto GAC media, while Greenstein et al (2018) did not report removal of sucralose as the GAC media was already exhausted. Cotinine is poorly removed by ozone and biodegradation and has shown to breakthrough in an 18‐min EBCT GAC at 12,500 BV (Kennedy, Reinert, Knappe, Ferrer, & Summers, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrient concentrations which have been both improved biofilter performance in some applications (Dhawan et al, 2017; Granger et al, 2014; Lauderdale et al, 2012) and resulted in negligible improvement in others (Azzeh et al, 2015; Fu et al, 2017; Nemani et al, 2018). Longer EBCTs which typically improve removals with diminishing returns (Arnold et al, 2018; Müller et al, 2017; Sundaram & Pagilla, 2020; Zearley & Summers, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…For removal of target trace chemical constituents, ozone system design is based on an ozone:total organic carbon (TOC) ratio. For disinfection of pathogens, system design is based on ozone residual concentrations and contact time (CT) (Sundaram & Pagilla, 2020). Ozone is extremely effective in Giardia inactivation and has been widely applied as a method for pathogen inactivation (Wickramanayake et al, 1984).…”
Section: Introductionmentioning
confidence: 99%